2019
DOI: 10.1038/s41598-019-47488-8
|View full text |Cite
|
Sign up to set email alerts
|

Colicin Z, a structurally and functionally novel colicin type that selectively kills enteroinvasive Escherichia coli and Shigella strains

Abstract: Colicin production in Escherichia coli ( E . coli ) strains represents an important trait with regard to microbial survival and competition in the complex intestinal environment. A novel colicin type, colicin Z (26.3 kDa), was described as a product of an original producer, extraintestinal E . coli B1356 strain, isolated from the anorectal abscess of a 17 years-old man. The 4,007 bp plasmid (pColZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Studies on the activity of bacteriocins, as an alternative to adjunctive therapy with antibiotics, and trials focused on probiotic bacteria are intensively conducted [31][32][33][34]. They concern mostly the bacteriocins of Gram-positive bacteria [35][36][37][38][39], but colicins and microcins are also tested as proteins with activity against pathogenic Gram-negative bacteria [40][41][42][43][44][45][46][47][48][49][50], including a few studies related to antibiotic-resistant strains [51,52]. However, nonclinical strains of animal origin, derived from farm animals that are particularly resistant to antibiotics, may reveal a distinct profile of sensitivity to bacteriocins.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the activity of bacteriocins, as an alternative to adjunctive therapy with antibiotics, and trials focused on probiotic bacteria are intensively conducted [31][32][33][34]. They concern mostly the bacteriocins of Gram-positive bacteria [35][36][37][38][39], but colicins and microcins are also tested as proteins with activity against pathogenic Gram-negative bacteria [40][41][42][43][44][45][46][47][48][49][50], including a few studies related to antibiotic-resistant strains [51,52]. However, nonclinical strains of animal origin, derived from farm animals that are particularly resistant to antibiotics, may reveal a distinct profile of sensitivity to bacteriocins.…”
Section: Introductionmentioning
confidence: 99%
“…These changes could reduce toxin production, lowering metabolic costs and elevating the fitness of the sessile population, thus maintaining diversity in sessile communities, and it allows for the dispersal of beneficial traits. As colicins are effective inhibitors to enteric pathogens [37,38], our findings could also be used to develop means for the successful and sustainable inhibition of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…They cross the intestinal barrier into the blood and reach other extraintestinal organs and cause the aggravation of the symptoms of the infection. Some studies have shown that bacteriocins (e.g., microcin and colicin) have an inhibitory effect on E. coli and Salmonella in vitro and can effectively reduce the numbers of E. coli (e.g., O157: H7) and Salmonella in the infected mice, improving the adverse effects caused by these pathogens [26][27][28]. In addition, some bacteriocins (e.g., subtilosin and gassericin E) have a significant inhibitory effect on the pathogens (e.g., Gardnerella vaginalis) which can cause the bacterial vaginal diseases [29,30].…”
Section: Functional Properties and Mechanisms Of Bacteriocinsmentioning
confidence: 99%